Snow, glass, apples - Gaiman, Neil (Dark Horse Books, 2019)
"A not-so-evil queen is terrified of her monstrous stepdaughter and determined to repel this creature and save her kingdom from a world where happy endings aren't so happily ever after. From the Hugo, Bram Stoker, Locus, World Fantasy, Nebula award-winning, and New York Times bestselling writer Neil Gaiman comes this graphic novel adaptation by Colleen Doran"--